Technological, Sensory, and Hypoglycemic Effects of Quinoa Flour Incorporation into Biscuits. (5th January 2022) - Alsuhaibani, Amnah Mohammed; Alkuraieef, Amal Nassir; Aljobair, Moneera Othman; Alshawi, Amal Hassan
Abstract : Background . Biscuits are consumed by all of society in the world. Incorporation of different ratios of quinoa flour into wheat flour for the production of biscuits is needed for the production of functional foods. Objective . This study aimed to evaluate the incorporation of 12.5% or 25% quinoa flour into biscuit production, evaluate rheological and sensory characteristics, and investigate the effect of the consumption of 20% cooked biscuits on diabetic rats. Design . The gross chemical composition, total carotenoids, phenolic and flavonoids of wheat flour and quinoa flour, and the rheological properties of the control, 12.5% quinoa, and 25% quinoa biscuit dough were determined. The effects of consumption of 12.5% quinoa and 25% quinoa biscuits on diabetic rats were investigated. Results . Quinoa flour had significantly higher levels of the gross chemical composition except for carbohydrate and increased phenolic compound and flavonoids content than those in wheat flour. Increasing the amount of quinoa flour in the biscuits could increase the farinograph and extensograph values of the dough. Biological results showed that the highest improvement in nutritional values appeared in the diabetic rat group, which consumed 25% quinoa biscuit for 60 days. The consumption of 12.5% quinoa biscuit and 25% quinoa biscuit showed a decline in blood glycosylated hemoglobin and glucose and an elevation in insulin levels compared with the positive control diabetic rat group. Discussion and Conclusion . It is encouraging to replace wheat flour with quinoa flour in biscuit manufacturing owing to positive effects on both the technological properties and sensory evaluation of biscuits. The increase of quinoa flour up to 25% had favorable nutritional values and hypoglycemic effects.